2015
DOI: 10.1073/pnas.1423869112
|View full text |Cite
|
Sign up to set email alerts
|

SLO3 auxiliary subunit LRRC52 controls gating of sperm KSPER currents and is critical for normal fertility

Abstract: Following entry into the female reproductive tract, mammalian sperm undergo a maturation process termed capacitation that results in competence to fertilize ova. Associated with capacitation is an increase in membrane conductance to both Ca 2+ and K + , leading to an elevation in cytosolic Ca 2+ critical for activation of hyperactivated swimming motility. In mice, the Ca 2+ conductance (alkalization-activated Ca 2+ -permeable sperm channel, CATSPER) arises from an ensemble of CATSPER subunits, whereas the K +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 49 publications
(81 reference statements)
1
62
0
Order By: Relevance
“…From published work, both loss- and gain-of-function potassium channel mutants had been linked to epilepsy. Among them, loss-of-function of Kv1.1, Kv1.2, Kv4.2 and Kv7.1, Kv7.2 potassium channels are associated with epilepsy (Brew et al, 2007; D’Adamo et al, 2013; Smart et al, 1998; Wang et al, 2015; Zeng et al, 2015). On the other hand, gain-of-function of the BK and Slack channel mutants are also linked with Epilepsy (Barcia et al, 2012; Du et al, 2005; Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…From published work, both loss- and gain-of-function potassium channel mutants had been linked to epilepsy. Among them, loss-of-function of Kv1.1, Kv1.2, Kv4.2 and Kv7.1, Kv7.2 potassium channels are associated with epilepsy (Brew et al, 2007; D’Adamo et al, 2013; Smart et al, 1998; Wang et al, 2015; Zeng et al, 2015). On the other hand, gain-of-function of the BK and Slack channel mutants are also linked with Epilepsy (Barcia et al, 2012; Du et al, 2005; Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When expressed in oocytes, the mouse channel is voltage dependent and sensitive to pH, being activated by alkalinization and suppressed by acidification (Schreiber et al, 1998;Zhang et al, 2006a,b). K Ca 5.1 is expressed selectively in sperm cells, and its properties are regulated by LRRC52, a testis-specific accessory subunit (Schreiber et al, 1998;Leonetti et al, 2012;Zeng et al, 2015). Evidence strongly suggests that it corresponds to the large-conductance potassium channel that can be recorded from mature sperm.…”
Section: K Ca 51-a Channel Specific To Sperm Cellsmentioning
confidence: 99%
“…It will be important to determine whether γ2–4 subunits also play any functional or physiological role in BK channel modulation in vivo. The mouse γ2 subunit has been found to function as an accessory subunit of the sperm- specific mouse Slo3 channels (Yang et al, 2011), and its ablation in mice was recently found to cause a severe fertility impairment (Zeng et al, 2015). It will be intriguing to determine whether in any stage of germ cells the γ2 subunit also modulates BK channels and whether Slo3 and BK channels can form functional heterotetrameric channels.…”
Section: Perspectivesmentioning
confidence: 99%